Literatur Review : Evaluasi Kebijakan Program oleh Balai Latihan Kerja Bagi Masyarakat di Jawa Timur - Muhammad Hafizh Pramata; Weni Rosdiana (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Evaluation of training programs at the UPT Balai Latihan Kerja (BLK) in East Java has become an essential component in measuring the success of competency-based training implementation that aligns with labor market needs. This study applies the Systematic Literature Review (SLR) method to answer the research questions regarding the effectiveness of training programs at UPT Balai Latihan Kerja (BLK) in East Java in improving work competencies, the evaluation models used in BLK training programs, and the challenges documented in the design of the evaluation studies. The literature search was conducted through Google Scholar using inclusion and exclusion criteria, guided by the research questions determined by the researcher, and a three-point Quality Assessment framework to assess the methodological rigor and contribution of each journal's evaluation results. From the five journals analyzed, the key findings indicate that BLK training programs in East Java are relevant to workforce development needs and implemented based on the Competency-Based Curriculum (Kurikulum Berbasis Kompetensi/KBK). This study contributes important insights to the understanding of vocational program evaluation at BLK, highlighting that current evaluation approaches possess structured and relevant implementation foundations, and generate a positive impact in supporting the improvement of work competencies among BLK participants and alumni, particularly in the East Java region.